2009
DOI: 10.1130/g25775a.1
|View full text |Cite
|
Sign up to set email alerts
|

Superheavy pyrite ( 34Spyr >  34SCAS) in the terminal Proterozoic Nama Group, southern Namibia: A consequence of low seawater sulfate at the dawn of animal life

Abstract: Sulfur isotope analysis (δ 34 S) of well-preserved carbonates spanning an ~10 Ma interval of the terminal Proterozoic Nama Group reveals that disseminated pyrite is consistently enriched in 34 S relative to coeval seawater sulfate as preserved in carbonate-associated sulfate (CAS). This observation is not consistent with the current paradigm for interpreting the geologic record of sulfur isotopes, which assumes that pyrite δ 34 S (δ 34 S pyr ) will be equal to or less than co-occurring CAS δ 34 S (δ 34 S CAS )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
126
7
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(146 citation statements)
references
References 24 publications
12
126
7
1
Order By: Relevance
“…A growing body of evidence also points to low-sulfate concentrations in Cambrian oceans relative to the modern (24,39). Low-sulfate conditions are indicated by prominent global excursions in the isotopic composition of seawater sulfate (39) and by the presence of "superheavy" δ 34 S of sedimentary pyrite in some settings (40). Low-sulfate conditions may have been promoted by the extensive burial of pyrite under widespread anoxic or dysoxic bottom waters (37) and by the lack of extensive bioturbation (41).…”
Section: Ocean Chemistry and The Cambrian Taphonomic Windowmentioning
confidence: 99%
“…A growing body of evidence also points to low-sulfate concentrations in Cambrian oceans relative to the modern (24,39). Low-sulfate conditions are indicated by prominent global excursions in the isotopic composition of seawater sulfate (39) and by the presence of "superheavy" δ 34 S of sedimentary pyrite in some settings (40). Low-sulfate conditions may have been promoted by the extensive burial of pyrite under widespread anoxic or dysoxic bottom waters (37) and by the lack of extensive bioturbation (41).…”
Section: Ocean Chemistry and The Cambrian Taphonomic Windowmentioning
confidence: 99%
“…Although extremely heavy pyrite δ 34 S values are not a worldwide signature in the ocean (e.g. Oman), it is clear that an extremely sulfate-depleted ocean is required to achieve these values (Ries et al, 2009 If secondary alteration induced the negative δ 13 C CARB trend observed in the lower Arena Fm, then the positive δ 13 C ORG trend (from -34‰ to -30‰) could be interpreted in two ways. Firstly, δ 13 C ORG could record a positive carbon isotope trend in the global exogenic carbon cycle.…”
Section: Characteristically Extreme δ 34 S Values In Pyritementioning
confidence: 99%
“…The sulfur isotope composition of marine pyrites, δ 34 S PY , rarely exceeds average Phanerozoic oceanic input (<8‰) (Halevy et al, 2012) simply because pyrite is the major sink for reduced sulfur that preferentially removes the lighter sulfur isotopes from the marine sulfate reservoir (Canfield, 2004 (Feng et al, 2010;Li et al, 2012;Ries et al, 2009). Although extremely heavy pyrite δ 34 S values are not a worldwide signature in the ocean (e.g.…”
Section: Characteristically Extreme δ 34 S Values In Pyritementioning
confidence: 99%
“…Reported δ 34 S pyrite values (24 -32.5 ‰ CDT) in the Loma Negra Formation are heavier than δ 34 S CAS for the same unit (24 -29 ‰, Bagnoud-Velásquez et al 2013). This "superheavy pyrites" have been interpreted for the coeval Nama Group (southern Africa) as the result of enhanced bacterial sulphate-reduction activity in a low sulphate environment, hinting at low atmospheric O 2 contents in the latest Ediacaran (Ries et al 2009). …”
Section: Sierras Bayas Group (Argentina)mentioning
confidence: 91%